PENJATUHAN PIDANA DAN PENERAPAN DAKWAAN TERHADAP TERDAKWA DALAM TINDAK PIDANA PENYALAHGUNAAN JABATAN SEBAGAI TINDAK PIDANA KORUPSI - Ruben Mula Mangatur; Radisman Saragih; Inri Januar (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
An act of corruption is an extraordinary crime that often occurs in Indonesia, the occurrence of this Corruption Crime can be done by someone because he has the authority and position that someone has. The impact that can arise due to the existence of a Corruption Crime, namely, it can cause problems in economic development in Indonesia, and can create poverty in the community of the country. In writing this thesis the author uses a normative legal research method, in which the author uses research on primary legal materials and secondary legal materials, then the author examines and draws a conclusion related to the problems studied by the author. The purpose of writing this thesis is to answer the imposition of criminal charges and the application of charges in the case of a criminal act of abuse of office as a criminal act of corruption. In writing this thesis, the author obtains answers regarding the problems studied by the author in the imposition of criminal charges and the application of charges against the accused.